Psychological and Social Consequences after Reconstruction of Upper Extremity Trauma: Methods of Detection and Management - Galanakos, Spyridon P.; Bot, Arjan G. J.; Zoubos, Aristides B.; Soucacos, Panayotis N. (Journal of Reconstructive Microsurgery, 2014)
Upper extremity trauma and resulting disability is a stressful event and can affect a patient's personality. Several studies have shown that this injury type has serious psychological and/or social consequences. We systematically reviewed the evidence on the consequences of disability after a complex trauma (combination of soft tissue, osseous, vascular, and nerve involvement) of the upper extremity. We tried to find out the potential crucial factors that could determine the final hand function. In addition, we considered the challenges that need to be addressed to eliminate the adverse or negative effects that arise from upper limb trauma. In the literature, there is a growing interest to study changes in patients' quality of life and return to work. Psychological morbidity is an important part of patients' perceived general health. These issues could play an important role in the final functional outcome of the therapy. An early identification and treatment of trauma-related distress in patients may prevent progression of psychological pathology and mitigate negative effects on general health status. It may be important to evaluate the amount of psychological distress when caring for patients with hand injuries.
Keywords: upper extremity complex trauma; disability; detection and prevention; psychological and social consequences